CYBERGOGY PARADIGM IN ARABIC LANGUAGE LEARNING AT ISLAMIC UNIVERSITIES DURING THE COVID-19 PANDEMIC - Musthofa, Tulus; Fauzi, Muhammad Sya'dullah (Arabi : Journal of Arabic Studies, 2021)
This paper aimed to examine the cybergogy paradigm in Arabic language learning at the college level, especially concerning the situation of the covid-19 pandemic. This study is a literature study exploring the application of cybergogy in Arabic language learning at the college level, especially concerning distance learning in the covid-19 pandemic. The primary sources in the literature review are journal articles of international reprisals such as Elsevier, Springer, Scopus, and nationally reputable and through books and various other sources relevant to research. The result of this study shows the concept of cybergogy in Arabic learning in Islamic universities during the covid-19 pandemic can be actualized by: 1) Virtual-based Bi'ah lughawiyyah, 2) Technology-based assignments, and 3) Technology-based evaluations. In addition, Arabic learning with the cybergogy paradigm is not only applied to integrate cognitive, emotional, and social aspects in a virtual learning space only, but also applied to integrate Arabic learning goals including mastery of four Arabic language skills.